Mitos Orang Muna Terhadap Danau Motonuno - Tiar Meniti; Wa Ode Sifatu (JURNAL KABANTI: Kerabat Antropologi, 2022)
This research is entitled ''The Myth of the Muna People Against Lake Motonuno''. The purpose of the study was to reveal the knowledge of the Muna people about the Myth of Lake Motonuno and the reasons for still maintaining this belief. This study reads the data with the thought of Radclive Brown, with the ethnographic method. The results of the study, the knowledge of the Muna people about Lake Motonuno as a sacred place that was passed down from generation to generation. The existence of Lake Motonuno is because people use it as a source of life so that it raises things that are taboo in the form of myths to maintain the wisdom of Lake Motonuno. This is in accordance with Radclive Brown's proposal on the term value ritual. Whatever a person in material terms, a place, a word or a name, an occasion or event, a day of the week or a period of year that is the object of a taboo avoidance ritual can be said to have a value ritual. Radclive Brown also states that there is a belief that violating a taboo will result in undesirable changes for the person who violates it. So, for generations, people still believe in the myth of Lake Motonuno.